Treatment choice in single‐sided deafness and asymmetric hearing loss. A prospective, multicentre cohort study on 155 patients. (26th March 2021) - Marx, Mathieu; Mosnier, Isabelle; Vincent, Christophe; Bonne, Nicolas‐Xavier; Bakhos, David; Lescanne, Emmanuel; Flament, Jonathan; Bernardeschi, Daniele; Sterkers, Olivier; Fraysse, Bernard; Lepage, Benoit; Godey, Benoit; et al.
Abstract: Objectives: To describe the treatment choice in a cohort of subjects with single‐sided deafness (SSD) and asymmetric hearing loss (AHL). To assess the reliability of the treatment trials. Design: In this national, multicentre, prospective study, the choice of subjects was made after two consecutive trials of Contralateral Routing Of the Signal (CROS) hearing aids and a Bone Conduction Device (BCD) on a headband. Subjects could proceed with one of these two options, opt for cochlear implantation or decline all treatments. Setting: Seven tertiary university hospitals. Participants: One hundred fifty‐five subjects with SSD or AHL fulfilling the candidacy criteria for cochlear implantation, with or without associated tinnitus. Main outcome measures: After the two trials, the number of subjects choosing each option was described. Repeated assessments of both generic and auditory‐specific quality of life were conducted, as well as hearing assessments (speech recognition in noise and horizontal localization). Results: CROS was chosen by 75 subjects, followed by cochlear implantation (n = 51), BCD (n = 18) and abstention (n = 11). Patients who opted for cochlear implantation had a poorer quality of life ( P  = .03). The improvement of quality of life indices after each trial was significantly associated with the final treatment choice ( P  = .008 for generic indices, P  = .002 for auditory‐specific indices). The follow‐up showed that this improvement had been overestimated in the CROS group, with a long‐term retention rate of 52.5%. Conclusions: More than one third of SSD/AHL subjects are unsatisfied after CROS and BCD trials. Repeated quality of life assessments help counselling the patient for his/her treatment choice.